A modified CeO2 filler and a high-performance thermoplastic plastic containing the filler and a preparation method thereof
By preparing modified CeO2 filler and blending it with thermoplastics, the problem of insufficient mechanical properties of thermoplastics in the prior art is solved, and its mechanical properties are significantly improved and its application field is expanded.
Patent Information
- Application Number
- CN202310474813.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-28
AI Technical Summary
In the prior art, it is difficult to meet the requirements of the mechanical properties of the material by using cerium dioxide alone, which limits the use of thermoplastics in certain application fields.
By preparing a modified CeO2 filler, the specific steps include reacting nano CeO2 with Si-902 and acetone in a water bath, followed by components such as Tris-HCl buffer solution, dopamine hydrochloride and octadecyldimethylmethoxysilane, etc. The reaction was carried out to form a PDA@CeO2-g-Si-902@octadecyldimethylmethoxysilane filler, and it was stirred and blended with the thermoplastic and extruded.
The mechanical properties of thermoplastics are improved, including tensile strength, flexural modulus and cantilever beam impact strength, expanding the scope of use of thermoplastics in application fields.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a modified CeO2 filler and a high-performance thermoplastic plastic containing the filler and a preparation method thereof. Background Art
[0002] Cerium dioxide (CeO2) has high chemical stability. When added to thermoplastics, it can improve the mechanical properties of thermoplastics. However, in some special application fields, it is difficult to meet the mechanical properties requirements of materials by simply using cerium dioxide to modify thermoplastics.
[0003] For this reason, the present invention synthesizes a self-made modified CeO2 to modify thermoplastics, which has better mechanical properties than directly modifying thermoplastics with commercially available nano-CeO2. Related literature has not been reported, which greatly expands the application field of thermoplastics and has very practical significance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a modified CeO2 filler and a preparation method of a high-performance thermoplastic plastic containing the filler, which has better mechanical properties and is of great significance.
[0005] The technical problem to be solved by the present invention is achieved through the following technical solutions:
[0006] A modified CeO2 filler is prepared by the following method:
[0007] (1) Weigh a certain amount of nano-CeO2, Si-902 (γ-aminopropylmethyldiethoxysilane), and acetone, put them into a reaction vessel, and react them in a water bath at 30-50°C for 8-12 hours to obtain solution A;
[0008] (2) Filtering, washing and drying solution A to obtain CeO2-g-Si-902;
[0009] (3) Weigh a certain amount of Tris solution and HCl solution, place them in a reaction vessel, and stir the reaction at room temperature for 6-8 hours to prepare a Tris-HCl buffer solution;
[0010] (4) Weigh a certain amount of Tris-HCl buffer solution, CeO2-g-Si-902, dopamine hydrochloride, octadecyldimethylmethoxysilane, deionized water, and crosslinker polypropylene glycol glycidyl ether, place in a reaction vessel, and react in a water bath at 50-70° C. for 10-16 h to obtain solution B;
[0011] (5) Solution B is filtered, washed, and dried to obtain PDA@CeO2-g-Si-902@octadecyldimethylmethoxysilane, which is a modified CeO2 filler.
[0012] Preferably, in step (1), the mass ratio of nano-CeO2, Si-902 (γ-aminopropylmethyldiethoxysilane) and acetone is (30-36): (10-16): (80-90).
[0013] Preferably, in step (3), the mass ratio of Tris solution to HCl solution is (30-40):(40-48).
[0014] Preferably, the mass ratio of Tris-HCl buffer solution, CeO2-g-Si-902, dopamine hydrochloride, octadecyldimethylmethoxysilane, deionized water, and crosslinking agent polypropylene glycol glycidyl ether in step (4) is (50-60):(20-24):(14-16):(16-18):(90-110):(0.4-0.8).
[0015] A high-performance thermoplastic containing modified CeO2 filler also includes thermoplastic, and the weight ratio of the modified CeO2 filler to the thermoplastic is 1:4-1:5.
[0016] Preferably, the thermoplastic plastic is polyethylene (PE), polypropylene (PP), nylon 6 (PA6), polybutylene terephthalate (PBT) or polystyrene (PS).
[0017] A method for preparing a high-performance thermoplastic comprises the following steps:
[0018] (1) Add the modified CeO2 filler into the thermoplastic and stir it in a high-speed mixer for 10-15 minutes;
[0019] (2) After stirring, the mixture is added into a twin-screw extruder for blending and extrusion to obtain a high-performance thermoplastic plastic.
[0020] Preferably, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0021] Application of modified CeO2 filler in automobile interior decoration.
[0022] A high-performance thermoplastic for automotive interior applications.
[0023] The above technical solution of the present invention has the following beneficial effects:
[0024] (1) DA can be oxidized and self-polymerized into PDA and deposited on the surface of CeO2-g-Si-902 to obtain a rough surface morphology. When added to CeO2-g-Si-902, PDA can be deposited not only on the surface of raw cotton, but also on the surface of CeO2-g-Si-902. The unique catechol structure of PDA can make the encapsulated nanoparticles negatively charged, and the strong electrostatic force can form an adhesion layer on the surface of CeO2-g-Si-902, thereby improving the bonding force between the two.
[0025] (2) The cross-linking agent polypropylene glycol glycidyl ether reacts with DA and the amino groups on the surface of CeO2-g-Si-902 to form a stable chemical bond between DA and CeO2-g-Si-902.
[0026] (3) After hydrolysis, octadecyldimethylmethoxysilane can produce a large number of Si-OH bonds, which react with the hydroxyl groups on the surface of PDA@CeO2-g-Si-902 to form stable Si-O-Si bonds, forming a three-dimensional network cross-linked structure, and finally forming PDA@CeO2-g-Si-902@octadecyldimethylmethoxysilane, which is modified CeO2.
[0027] (4) The modified CeO2 synthesized in this patent is used to modify thermoplastics. Compared with commercially available nano-CeO2, the mechanical properties of thermoplastics are better. This is because: 1) Compared with commercially available nano-CeO2, the modified CeO2 synthesized in this patent is not easy to agglomerate due to the presence of Si-902, and the unique catechol structure of PDA also makes it more compatible with thermoplastics and has better mechanical properties. 2) The modified CeO2 synthesized in this patent is a three-dimensional network cross-linked structure, which is more conducive to improving the mechanical properties of thermoplastics. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.
[0029] The raw materials used in the embodiments of the present invention are as follows:
[0030] PBT (model 2002U), Polyplastics, Japan; PP (model T30S), Daqing Petrochemical; PE (model 5070), Panjin Ethylene; PA6 (model CM1017), Toray, Japan; PS (model 350), Guoqiao, China Taiwan; deionized water, Jinan Hairuibao Chemical Co., Ltd.; nano-CeO2, Ganzhou Zhanhai New Material Technology Co., Ltd.; Si-902 (γ-aminopropylmethyldiethoxysilane), Nanjing Aocheng Chemical; acetone, Henan Hongrun Chemical Co., Ltd.; Tris solution, Hubei Kewode Chemical Co., Ltd.; HCl solution, Beijing Haifuda Technology Co., Ltd.; dopamine hydrochloride, Nanjing Wanghua Chemical Technology Co., Ltd.; octadecyl dimethyl methoxy silane, Hubei Tosoh Chemical Technology Co., Ltd.; polypropylene glycol glycidyl ether, Shanghai Rufa Chemical Technology Co., Ltd.
[0031] The testing instrument used in the present invention is as follows:
[0032] ZSK30 twin-screw extruder, W&P, Germany; JL-1000 tensile testing machine, Guangzhou Guangcai Experimental Instrument Co., Ltd.; HTL900-T-5B injection molding machine, Haitai Plastic Machinery Co., Ltd.; XCJ-500 impact testing machine, Chengde Testing Machine Factory; QT-1196 tensile tester, Dongguan Gaotai Testing Instrument Co., Ltd.; QD-GJS-B12K high-speed mixer, Beijing Hengaode Instrument Co., Ltd.
[0033] Example 1
[0034] (I) Preparation of modified CeO2 filler:
[0035] (1) Weigh 300 g of nano-CeO2, 100 g of Si-902 (γ-aminopropylmethyldiethoxysilane), and 800 g of acetone, put them into a reaction vessel, and react them in a 30°C water bath for 8 h to obtain solution A;
[0036] (2) Filtering, washing and drying solution A to obtain CeO2-g-Si-902;
[0037] (3) Weigh 300 g of Tris solution and 400 g of HCl solution, place them in a reaction vessel, and stir and react for 6 h at room temperature to prepare a Tris-HCl buffer solution;
[0038] (4) Weigh 500 g of Tris-HCl buffer solution, 200 g of CeO2-g-Si-902, 140 g of dopamine hydrochloride, 160 g of octadecyldimethylmethoxysilane, 900 g of deionized water, and 4 g of cross-linking agent polypropylene glycol glycidyl ether, place in a reaction vessel, and react in a 50° C. water bath for 10 h to obtain solution B;
[0039] (5) Filter, wash and dry the solution B to obtain modified CeO2 filler M1.
[0040] (II) Preparation of high performance thermoplastics:
[0041] 20 parts of M1 were added to 80 parts of polypropylene (PP), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PP composite material X1.
[0042] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0043] Comparative Example 1
[0044] 20 parts of commercially available nano-CeO2 were added to 80 parts of polypropylene (PP), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PP composite material D1.
[0045] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
[0046] The mechanical properties of the PP composite materials prepared in Example 1 and Comparative Example 1 are shown in the following table:
[0047] Test items Test Standards unit X1 D1 Tensile Strength ASTM D638 MPa 15.3 12.3 Flexural modulus ASTM D790 MPa 1560 1210 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 5.3 2.8
[0048] It can be seen from the above table:
[0049] The tensile strength, bending strength and cantilever beam impact strength of X1 are greater than those of D1, which indicates that the mechanical properties of PP modified by adding the modified CeO2 filler of the present invention are better than that of PP modified by simply adding commercially available nano-CeO2.
[0050] Example 2
[0051] (I) Preparation of modified CeO2 filler:
[0052] (1) Weigh 360 g of nano-CeO2, 160 g of Si-902 (γ-aminopropylmethyldiethoxysilane), and 900 g of acetone, put them into a reaction vessel, and react them in a 50°C water bath for 12 h to obtain solution A;
[0053] (2) Filtering, washing and drying solution A to obtain CeO2-g-Si-902;
[0054] (3) Weigh 400 g of Tris solution and 480 g of HCl solution, place them in a reaction vessel, and stir and react at room temperature for 8 h to prepare a Tris-HCl buffer solution;
[0055] (4) Weigh 600 g of Tris-HCl buffer solution, 240 g of CeO2-g-Si-902, 160 g of dopamine hydrochloride, 180 g of octadecyldimethylmethoxysilane, 1.1 kg of deionized water, and 8 g of cross-linking agent polypropylene glycol glycidyl ether, place in a reaction vessel, and react in a 70° C. water bath for 16 h to obtain solution B;
[0056] (5) Filter, wash and dry the solution B to obtain modified CeO2 filler M2.
[0057] (II) Preparation of high performance thermoplastics:
[0058] 20 parts of M2 were added to 80 parts of polybutylene terephthalate (PBT), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PBT composite material X2.
[0059] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 300r / min.
[0060] Comparative Example 2
[0061] 20 parts of commercially available nano-CeO2 were added to 80 parts of polybutylene terephthalate (PBT), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PBT composite material D2.
[0062] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 300r / min.
[0063] The mechanical properties of the PBT composite materials prepared in Example 2 and Comparative Example 2 are shown in the following table:
[0064] Test items Test Standards unit X2 D2 Tensile Strength ASTM D638 MPa 71.8 59.1 Flexural modulus ASTM D790 MPa 3330 2580 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 5.6 2.5
[0065] It can be seen from the above table:
[0066] The tensile strength, bending strength and cantilever beam impact strength of X2 are greater than those of D2, which indicates that the mechanical properties of PBT modified by adding the modified CeO2 filler of the present invention are better than that of PBT modified by simply adding commercially available nano-CeO2.
[0067] Example 3
[0068] (I) Preparation of modified CeO2 filler:
[0069] (1) Weigh 330 g of nano-CeO2, 130 g of Si-902 (γ-aminopropylmethyldiethoxysilane), and 850 g of acetone, put them into a reaction vessel, and react them in a 40°C water bath for 10 h to obtain solution A;
[0070] (2) Filtering, washing and drying solution A to obtain CeO2-g-Si-902;
[0071] (3) Weigh 350 g of Tris solution and 440 g of HCl solution, place them in a reaction vessel, and stir and react at room temperature for 7 h to prepare a Tris-HCl buffer solution;
[0072] (4) Weigh 550 g of Tris-HCl buffer solution, 220 g of CeO2-g-Si-902, 150 g of dopamine hydrochloride, 170 g of octadecyldimethylmethoxysilane, 1.0 kg of deionized water, and 6 g of cross-linking agent polypropylene glycol glycidyl ether, place in a reaction vessel, and react in a 60° C. water bath for 13 h to obtain solution B;
[0073] (5) Solution B is filtered, washed, and dried to obtain modified CeO2 filler M3.
[0074] (II) Preparation of high performance thermoplastics:
[0075] 20 parts of M3 were added to 80 parts of polyethylene (PE), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PE composite material X3.
[0076] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0077] Comparative Example 3
[0078] 20 parts of commercially available nano-CeO2 were added to 80 parts of polyethylene (PE), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PE composite material D3.
[0079] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0080] The mechanical properties of the PE composite materials prepared in Example 3 and Comparative Example 3 are shown in the following table:
[0081] Test items Test Standards unit X3 D3 Tensile Strength ASTM D638 MPa 13.9 10.4 Flexural modulus ASTM D790 MPa 1490 1145 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 4.6 1.8
[0082] It can be seen from the above table:
[0083] The tensile strength, bending strength and cantilever beam impact strength of X3 are greater than those of D3, which indicates that the mechanical properties of PE modified by adding the modified CeO2 filler of the present invention are better than that of PE modified by simply adding commercially available nano-CeO2.
[0084] Example 4
[0085] (I) Preparation of modified CeO2 filler:
[0086] (1) Weigh 335 g of nano-CeO2, 155 g of Si-902 (γ-aminopropylmethyldiethoxysilane), and 865 g of acetone, put them into a reaction vessel, and react them in a 45°C water bath for 11 h to obtain solution A;
[0087] (2) Filtering, washing and drying solution A to obtain CeO2-g-Si-902;
[0088] (3) Weigh 365 g of Tris solution and 455 g of HCl solution, place them in a reaction vessel, and stir and react at room temperature for 8 h to prepare a Tris-HCl buffer solution;
[0089] (4) Weigh 515 g of Tris-HCl buffer solution, 235 g of CeO2-g-Si-902, 155 g of dopamine hydrochloride, 175 g of octadecyldimethylmethoxysilane, 965 g of deionized water, and 5.5 g of cross-linking agent polypropylene glycol glycidyl ether, place in a reaction vessel, and react in a 55° C. water bath for 15 h to obtain solution B;
[0090] (5) Solution B is filtered, washed, and dried to obtain modified CeO2 filler M4.
[0091] (II) Preparation of high performance thermoplastics:
[0092] 20 parts of M4 were added to 80 parts of polyamide 6 (PA6), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PA6 composite material X4.
[0093] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 130°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 250°C, and the screw speed is 320r / min.
[0094] Comparative Example 4
[0095] 20 parts of commercially available nano-CeO2 were added to 80 parts of polyamide 6 (PA6), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PA6 composite material D4.
[0096] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 130°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 250°C, and the screw speed is 320r / min.
[0097] The mechanical properties data of the PA6 composite materials prepared in the above Example 4 and Comparative Example 4 are shown in the following table:
[0098] Test items Test Standards unit X4 D4 Tensile Strength ASTM D638 MPa 78.4 66.2 Flexural modulus ASTM D790 MPa 3350 2610 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 6.9 2.7
[0099] It can be seen from the above table:
[0100] The tensile strength, bending strength and cantilever beam impact strength of X4 are greater than those of D4, which indicates that the mechanical properties of PA6 modified by adding the modified CeO2 filler of the present invention are better than those simply adding commercially available nano-CeO2.
[0101] Example 5
[0102] (I) Preparation of modified CeO2 filler:
[0103] (1) Weigh 345 g of nano-CeO2, 135 g of Si-902 (γ-aminopropylmethyldiethoxysilane), and 815 g of acetone, put them into a reaction vessel, and react them in a 45°C water bath for 11 h to obtain solution A;
[0104] (2) Filtering, washing and drying solution A to obtain CeO2-g-Si-902;
[0105] (3) Weigh 395 g of Tris solution and 475 g of HCl solution, place in a reaction vessel, and stir at room temperature for 8 h to prepare a Tris-HCl buffer solution;
[0106] (4) Weigh 535 g of Tris-HCl buffer solution, 215 g of CeO2-g-Si-902, 145 g of dopamine hydrochloride, 165 g of octadecyldimethylmethoxysilane, 955 g of deionized water, and 6.5 g of cross-linking agent polypropylene glycol glycidyl ether, place in a reaction vessel, and react in a 65° C. water bath for 16 h to obtain solution B;
[0107] (5) Solution B is filtered, washed, and dried to obtain modified CeO2 filler M5.
[0108] (II) Preparation of high performance thermoplastics:
[0109] 20 parts of P5 were added to 80 parts of styrene (PS), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PS composite material X5.
[0110] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 160°C, the temperature of the second temperature zone is 200°C, the temperature of the third temperature zone is 200°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 200°C, the head temperature of the twin-screw extruder is 200°C, and the screw speed is 280r / min.
[0111] Comparative Example 5
[0112] 20 parts of commercially available nano-CeO2 were added to 80 parts of styrene (PS), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PS composite material D5.
[0113] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 160°C, the temperature of the second temperature zone is 200°C, the temperature of the third temperature zone is 200°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 200°C, the head temperature of the twin-screw extruder is 200°C, and the screw speed is 280r / min.
[0114] The mechanical properties data of the PS composite materials prepared in the above Example 5 and Comparative Example 5 are shown in the following table:
[0115] Test items Test Standards unit X5 D5 Tensile Strength ASTM D638 MPa 59.8 47.2 Flexural modulus ASTM D790 MPa 4090 3210 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 5.9 2.9
[0116] It can be seen from the above table:
[0117] The tensile strength, bending strength and cantilever beam impact strength of X5 are greater than those of D5, which indicates that the mechanical properties of PS modified by adding the modified CeO2 filler of the present invention are better than those of PS modified by simply adding commercially available nano-CeO2.
[0118] This patent describes a modified CeO2 filler and a preparation method of a high-performance thermoplastic plastic containing the filler. The mechanical properties of the prepared thermoplastic plastic are improved to a certain extent, which greatly expands the application field of thermoplastic plastics and is of great significance.
[0119] Although the present invention has been disclosed as above by the embodiments, it is not intended to limit the present invention. Any person skilled in the art may make various choices and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention is limited by the claims and their equivalents.
Claims
1. A modified CeO2 filler, characterized in that: The modified CeO2 filler is prepared by the following method: (1) Weigh a certain amount of nano-CeO2, Si-902, and acetone, put them into a reaction vessel, and react them in a water bath at 30-50°C for 8-12 hours to obtain solution A; wherein the mass ratio of nano-CeO2, Si-902, and acetone is (30-36): (10-16): (80-90); (2) Filtering, washing and drying solution A to obtain CeO2-g-Si-902; (3) Weigh a certain amount of Tris solution and HCl solution, place them in a reaction vessel, and stir the reaction at room temperature for 6-8 hours to prepare a Tris-HCl buffer solution; wherein the mass ratio of the Tris solution to the HCl solution is (30-40):(40-48); (4) Weigh a certain amount of Tris-HCl buffer solution, CeO2-g-Si-902, dopamine hydrochloride, octadecyl dimethyl methoxy silane, deionized water, and crosslinker polypropylene glycol glycidyl ether, place them in a reaction vessel, and react in a 50-70° C. water bath for 10-16 hours to obtain solution B; wherein the mass ratio of Tris-HCl buffer solution, CeO2-g-Si-902, dopamine hydrochloride, octadecyl dimethyl methoxy silane, deionized water, and crosslinker polypropylene glycol glycidyl ether is (50-60): (20-24): (14-16): (16-18): (90-110): (0.4-0.8); (5) Solution B is filtered, washed, and dried to obtain PDA@CeO2-g-Si-902@octadecyldimethylmethoxysilane, which is a modified CeO2 filler.
2. A high-performance thermoplastic comprising the modified CeO2 filler according to claim 1, characterized in that: It also includes thermoplastic plastics, and the weight ratio of the modified CeO2 filler to the thermoplastic plastics is 1:4-1:
5.
3. The high performance thermoplastic according to claim 2, characterized in that The thermoplastic plastic is polyethylene (PE), polypropylene (PP), nylon 6 (PA6), polybutylene terephthalate (PBT) or polystyrene (PS).
4. The method for preparing a high-performance thermoplastic according to any one of claims 2 to 3, characterized in that: The following steps are involved: (1) Add the modified CeO2 filler into the thermoplastic and stir it in a high-speed mixer for 10-15 minutes; (2) After stirring, the mixture is added into a twin-screw extruder for blending and extrusion to obtain a high-performance thermoplastic plastic.
5. The method for preparing a high-performance thermoplastic according to claim 4, characterized in that: The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.
6. Use of the modified CeO2 filler according to claim 1 in automobile interior decoration.
7. Use of the high-performance thermoplastic plastic according to any one of claims 2 to 3 or the high-performance thermoplastic plastic prepared by the preparation method according to any one of claims 4 to 5 in automobile interior decoration.
Citation Information
Patent Citations
Easily secondarily modified polydopamine coated modified calcium carbonate powder with high reaction activity and preparation method of powder
CN106590044A
Anti-ultraviolet polypropylene composition and polypropylene and polypropylene film prepared from composition
CN107383595A